2021
DOI: 10.1101/2021.02.08.430339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of the human SAGA coactivator complex: The divergent architecture of human SAGA allows modular coordination of transcription activation and co-transcriptional splicing

Abstract: Human SAGA is an essential co-activator complex that regulates gene expression by interacting with enhancer-bound activators, recruiting transcriptional machinery, and modifying chromatin near promoters. Subunit variations and the metazoan-specific requirement of SAGA in development hinted at unique structural features of the human complex. Our 2.9 Angstrom structure of human SAGA reveals intertwined functional modules flexibly connected to a core that distinctively integrates mammalian paralogs, incorporates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 86 publications
2
14
0
Order By: Relevance
“…Taken together, these results suggest that TRRAP does not have a major contribution to SAGA integrity and function at these genes. Thus, despite its large size and absence of catalytic activity, TRRAP is presumably not a core subunit of SAGA in human cells, consistent with recent structural studies revealing its peripheral localization within the complex (59)(60)(61).…”
Section: Saga Regulates Unfolded Protein Response Genes Independently Of Trrapsupporting
confidence: 86%
“…Taken together, these results suggest that TRRAP does not have a major contribution to SAGA integrity and function at these genes. Thus, despite its large size and absence of catalytic activity, TRRAP is presumably not a core subunit of SAGA in human cells, consistent with recent structural studies revealing its peripheral localization within the complex (59)(60)(61).…”
Section: Saga Regulates Unfolded Protein Response Genes Independently Of Trrapsupporting
confidence: 86%
“…Deletion of yeast KAT or DUB module subunits only interfered with the assembly of the corresponding module. Recent structural studies by high resolution cryo-electron microscopy revealed that the connections of the core module to the two enzymatic modules are considerably flexible in both yeast and human SAGA complexes [ 22 , 23 , 33 ]. The carboxyl-terminal part of Sgf73 is embedded in the core module, thereby tethering the DUB module to the remainder of SAGA.…”
Section: Saga Composition Across Kingdomsmentioning
confidence: 99%
“…Unlike other GCN5-containing complexes such as the metazoan-specific ATAC complex, SAGA is uniquely conserved in all eukaryotes. The recently elucidated high-resolution structures of SAGA from two yeast genera and from humans enlightened our understanding of its dynamic conformation in unicellular and higher eukaryotes [ 22 , 23 , 33 ]. Attributable to its intrinsic large composition and structural flexibility of the KAT and DUB modules in relation to the core module, each module may have independent roles in the process of transcriptional regulation, which is consistent with different impacts to gene expression profiles upon mutation of components belonging to separate modules [ 70 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The modified GO coating method has been used with several other samples of varying size, and typically resulted in reconstructions with better than 3Å resolution 54 ( to be published ). However, it should be noted that in these other cases, tilting was not required.…”
Section: Introductionmentioning
confidence: 99%